Legal Analysis Of The Effectiveness Of The Icsid Arbitration Institution As A Means Of Resolving Foreign Investment Disputes In Indonesia - Anggusti, Martono; Siallagan, Haposan; Hutabarat, Dwi Natalia Martama (Jurnal Ilmu Sosial Mamangan, 2024)
Resolving disputes related to foreign investment is not as straightforward as one might think, as it involves investment disputes that engage two or more legal systems. Therefore, the resolution is not solely determined by the law applicable within the territory of Indonesia, but also takes into account the laws of other countries participating in the convention. When a settlement between the parties cannot be reached, the dispute can be resolved through an arbitration body designated by the parties to facilitate the resolution or through conventional judicial bodies in accordance with their authority as regulated by legislation. Alternative dispute resolution through arbitration will be more efficient and effective as it is achieved through deliberation and consensus or a win-win solution. This research is descriptive in nature, aiming to provide an overview or description of the law on divestment in foreign companies in Indonesia. As a descriptive study, a normative approach is used, focusing on the examination of legal principles, legal systems, vertical and horizontal synchronization of legislation, and legal history. The Bilateral Investment Treaty (BIT) serves as a legal basis that needs to be revised. The initial role of this agreement was to attract investors to enter Indonesia, with the hope of reaching a balanced agreement between the two countries. However, in practice, the BIT has become the foundation relied upon by foreign investors in Indonesia. The recommendation made in this study is that the Government of the Republic of Indonesia, in establishing Bilateral Investment Treaties, must include clear provisions so that the description of the agreement does not overlap with the positive law already established in Indonesia.